Evolution of antioxidant peptides and their proteomic homology during processing of Jinhua ham. (15th August 2022) - Li, Ping; Xu, Feiran; Zhou, Hui; Gao, Yafei; Zhu, Hanlin; Nie, Wen; Wang, Zhaoming; Wang, Ying; Deng, Jieying; Zhou, Kai; Xu, Baocai
Abstract: This study aimed to clarify the evolution of antioxidant peptides and their proteomic homology during a continuous period of Jinhua ham processing. The peptide content increased during the process, reaching a value of 1.92% (weight %, based on meat weight) in ham at the end of dry-ripening, which was approximately 8-fold higher than that prior to salting. From scavenging effects on 1, 1-diphenyl-2-picrylhydrazyl radical (DPPH) and hydroxyl radical (OH) and chelating ability on Fe 2+, it was suggested that peptides generated at the end of dry-ripening had the highest level of antioxidant activity. Size-exclusion chromatography indicated that the antioxidation of peptides might be related to their MWs, where more fractions with small MWs result in higher antioxidant activity. The results of endogenous protease activities showed 22.33% of the initial activities of Cathepsin B were retained, suggesting that Cathepsin B plays a key role in the formation of antioxidant peptides. Homology-based proteomics showed that peptides primarily arose from myosin (32.37%), followed by actin (16.91%), troponin T (12.08%) and others. Highlights: The antioxidant peptides at different processing stages of Jinhua ham were evaluated. More peptides fractions with small MWs result in higher antioxidant activity. Cathepsin B plays a key role in the formation of antioxidant peptides. Antioxidant peptides primarily arise from myosin, actin and troponin T.